Spatial presentation of biological molecules to cells by localized diffusive transfer. Issue 12 (21st May 2019) - Regier, Mary C.; Olszewski, Emily; Carter, Christoph C.; Aitchison, John D.; Kaushansky, Alexis; Davis, Jennifer; Berthier, Erwin; Beebe, David J.; Stevens, Kelly R.
Abstract : We present a straightforward approach for controlling soluble factor patterning in open in vitro cultures. Abstract : Cellular decisions in human development, homeostasis, regeneration, and disease are coordinated in large part by signals that are spatially localized in tissues. These signals are often soluble, such that biomolecules produced by one cell diffuse to receiving cells. To recapitulate soluble factor patterning in vitro, several microscale strategies have been developed. However, these techniques often introduce new variables into cell culture experiments ( e.g., fluid flow) or are limited in their ability to pattern diverse solutes in a user-defined manner. To address these challenges, we developed an adaptable method that facilitates spatial presentation of biomolecules across cells in traditional open cultures in vitro . This technique employs device inserts that are placed in standard culture wells, which support localized diffusive pattern transmission through microscale spaces between device features and adherent cells. Devices can be removed and cultures can be returned to standard media following patterning. We use this method to spatially control cell labeling with pattern features ranging in scale from several hundred microns to millimeters and with sequential application of multiple patterns. To better understand the method we investigate relationships between pattern fidelity, device geometry, and consumption and diffusion kinetics using finite element modeling. We then apply the method to spatially defining reporter cell heterogeneity by patterning a small molecule modulator of genetic recombination with the requisite sustained exposure. Finally, we demonstrate use of this method for patterning larger and more slowly diffusing particles by creating focal sites of gene delivery and infection with adenoviral, lentiviral, and Zika virus particles. Thus, our method leverages devices that interface with standard culture vessels to pattern diverse diffusible factors, geometries, exposure dynamics, and recipient cell types, making it well poised for adoption by researchers across various fields of biological research.